RACE, GENDER, MIGRATION, AND INEQUALITY IN CONTEMPORARY AMERICAN FICTION - Aygun Hasanova (ELITERATE : Journal of English Linguistics and Literature Studies, 2026)
Questions of identity remain central to contemporary American and diasporic fiction because racial history, gendered expectations, migration, and material inequality shape both self-understanding and social recognition. Existing studies commonly examine these dimensions or authors separately, leaving limited comparative analysis of how they interact across narratives of enslavement and transnational mobility. This article compares Toni Morrison's Beloved, Colson Whitehead's The Underground Railroad, Jhumpa Lahiri's The Namesake, and Chimamanda Ngozi Adichie's Americanah. It asks how the novels construct identity through race, gender, migration, and social inequality and what their juxtaposition contributes to literary studies of identity. A qualitative comparative design combines close reading, thematic coding, and cross-text interpretation informed by Hall's cultural identity, Bhabha's hybridity, Butler's gender performativity, and Crenshaw's intersectionality. The analysis identifies four interrelated patterns: racial identity is produced through historical memory and institutional definition; gender is embodied through repeated social practices and constrained forms of agency; migrant belonging develops through naming, language, hair, domestic practice, and cultural translation; and inequality determines whose identity is recognized, disciplined, or rendered precarious. Across the corpus, identity is neither an autonomous possession nor unrestricted fluidity. It is a negotiated position formed through memory, place, embodiment, and unequal power. The comparative framework therefore connects neo-slave and migration narratives while showing that resistance involves reclaiming interpretive authority over the meanings imposed on racialized and migrant subjects.